From the Cover: Tetrachlorobenzoquinone Exerts Neurological Proinflammatory Activity by Promoting HMGB1 Release, Which Induces TLR4 Clustering within the Lipid Raft. (13th July 2016) - Fu, Juanli; Shi, Qiong; Song, Xiufang; Liu, Zixuan; Wang, Yawen; Wang, Yuxin; Song, Erqun; Song, Yang
Abstract: Tetrachlorobenzoquinone (TCBQ) is a confirmed active metabolite of a well-known environmental pollutant pentachlorophenol (PCP). Unfortunately, there is insufficient knowledge present available on TCBQ's toxicity. Our previous studies indicated that TCBQ induces inflammatory response in vivo and in vitro ; however, its exact mechanism needs further investigation. Toll-like receptors (TLRs) play a crucial role in conveying of inflammatory signaling, whilst high-mobility group box 1 (HMGB1) functions as a transcription-enhancing nuclear protein that regulates inflammation. Indeed, this study demonstrated that TCBQ induces the secretion/translocation of HMGB1, which in turn activates its receptors, TLR family gene (especially TLR4) and receptor for advanced glycation end-products (RAGE) expressions. Consistently, the binding affinity of HMGB1 with its receptors also increased. In the case of HMGB1 or TLR4 deficiency, there were decreases in TCBQ-induced neuroinflammatory cytokine production and neuropathological changes, eg, neuronal loss, astrocyte and macrophage cells activation. Moreover, we found the mobilization of TLR4 into lipid rafts occurs in response to TCBQ exposure, lipid rafts disruptors weakened this effect, suggested lipid rafts play an essential role for TLR4-mediated signal transduction and target inflammatory cytokines expressions. In summary, our current findings revealed a previously unknown mechanism of TCBQ-induced neurological inflammation related to HMGB1-TLR4 signaling.